Wrist and forearm postures and motions during typing. - Serina ER; Tal R; Rempel D (Ergonomics)
Awkward upper extremity postures and repetitive wrist motions have been identified by some studies as risk factors for upper extremity musculoskeletal disorders during keyboard work. However, accurate body postures and joint motions of typists typing on standardized workstations are not known. A laboratory study was conducted to continuously measure wrist and forearm postures and motions of 25 subjects while they typed for 10 - 15 min at a standard computer workstation adjusted to the subjects' anthropometry. Electrogoniometers continuously recorded wrist and forearm angles. Joint angular velocities and accelerations were calculated from the postural data. The results indicate that wrist and forearm postures during typing were sustained at non-neutral angles; mean wrist extension angle was 23.4 +/- 10.9 degrees on the left and 19.9 +/- 8.6 degrees on the right. Mean ulnar deviation was 14.7 +/- 10.1 degrees on the left and 18.6 +/- 5.8 degrees on the right. More than 73% of subjects typed with the left or right wrist in greater than 15 degrees extension and more than 20% typed with the left or right wrist in greater than 20 degrees ulnar deviation. Joint angles and motions while typing on an adjusted computer workstation were not predictable based on anthropometry or typing speed and varied widely between subjects. Wrist motions are rapid and are similar in magnitude to wrist motions of industrial workers performing jobs having a high risk for developing cumulative trauma disorders. The magnitude of the dynamic components suggests that wrist joint motions may need to be evaluated as a risk factor for musculoskeletal disorders during typing.